Fabrication of Au25(SG)18–ZIF‐8 Nanocomposites: A Facile Strategy to Position Au25(SG)18 Nanoclusters Inside and Outside ZIF‐8. Issue 6 (22nd December 2017) - Luo, Yucheng; Fan, Shiyan; Yu, Wenqian; Wu, Zili; Cullen, David A.; Liang, Chaolun; Shi, Jianying; Su, Chengyong
Abstract: Multifunctional composite materials are currently highly desired for sustainable energy applications. A general strategy to integrate atomically precise Au25 (SG)18 with ZIF‐8 (Zn(MeIm)2, MeIm = 2‐methylimidazole), is developed via the typical Zn‐carboxylate type of linkage. Au25 (SG)18 are uniformly encapsulated into a ZIF‐8 framework (Au25 (SG)18 @ZIF‐8) by coordination‐assisted self‐assembly. In contrast, Au25 (SG)18 integrated by simple impregnation is oriented along the outer surface of ZIF‐8 (Au25 (SG)18 /ZIF‐8). The porous structure and thermal stability of these nanocomposites are characterized by N2 adsorption–desorption isothermal analysis and thermal gravimetric analysis. The distribution of Au25 (SG)18 in the two nanocomposites is confirmed by electron microscopy, and the accessibility of Au25 (SG)18 is evaluated by the 4‐nitrophenol reduction reaction. The as‐prepared nanocomposites retain the high porosity and thermal stability of the ZIF‐8 matrix, while also exhibiting the desired catalytic and optical properties derived from the integrated Au25 (SG)18 nanoclusters (NCs). Au25 (SG)18 @ZIF‐8 with isolated Au25 sites is a promising heterogenous catalyst with size selectivity imparted by the ZIF‐8 matrix. The structural distinction between Au25 (SG)18 @ZIF‐8 and Au25 (SG)18 /ZIF‐8 determines their different emission features, and provides a new strategy to adjust the optical behavior of Au25 (SG)18 for applications in bioimaging and biotherapy. Abstract : The controlled embedding of nanoclusters into metal–organic frameworks is one of the major obstacles for the application of nanoclusters in catalysis. A general strategy to position Au25 (SG)18 inside and outside ZIF‐8 (Zn(MeIm)2, MeIm = 2‐methylimidazole) is developed via the typical Zn‐carboxylate type of linkage. The catalytic and optical properties of such nanocomposites are further investigated.